Effects of high free ammonia concentrations on the performances of anaerobic bioreactors - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (ELSEVIER SCI LTD, 2005)
UASB reactors inoculated with different seed sludges were operated for 450 days under high ammonia concentrations to investigate inhibition effects. Reactors were fed with synthetic wastewater providing an organic loading of about 1.2 kg COD m(3) /day and having total ammonia nitrogen (TAN) concentrations gradually increasing from 1000 to 6000 mg/l. As, corresponding free ammonia nitrogen (FAN) concentrations elevated up to 800 mg/l, COD removal efficiencies in the range of 78-96% were determined. High removal efficiencies revealed that seed sludges taken from anaerobic reactors treating considerably low ammonia containing wastewaters have adapted to elevated free ammonia concentrations successfully. However, propionate accumulation in some reactors and decrease in eubacterial signals detected by fluorescent in situ hybridization (FISH) indicated that propionate degrading acetogenic bacteria are more sensitive than methanogenic archaea to free ammonia. Differences in the efficiencies of reactors were correlated with the quantity of resistant and sensitive microorganisms dominated in the reactors. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: acetogenic bacteria; ammonia; butyrate; inhibition; propionate; UASB reactor; METHANOGENIC SLUDGE; DIGESTION; INHIBITION; TOXICITY; LEACHATE; NITROGEN; MANURE; PH; WASTEWATERS; ADAPTATION